Cover Image, Volume 6, Issue 5. (12th August 2016) - Zhang, Xiaofeng; Cheung, William K.; Ye, Yunming
Abstract : The cover image, by Xiaofeng Zhang et al., is based on the Focus Article Mining from distributed and abstracted data, DOI: 10.1002/widm.1182 . Abstract : The cover image, by Xiaofeng Zhang et al., is based on the Focus Article Mining from distributed and abstracted data, DOI: 10.1002/widm.1182 .